State-of-the-art therapeutic strategies for targeting cancer stem cells in prostate cancer - Ramesh, Saravanan; Selvakumar, Preethi; Ameer, Mohamed Yazeer; Lian, Sen; Abdullah Alzarooni, Abdulqadir Ismail M.; Ojha, Shreesh; Mishra, Anshuman; Tiwari, Ashutosh; Kaushik, Ajeet; Jung, Young Do; Chouaib, Salem; Lakshmanan, Vinoth-Kumar (Frontiers in Oncology, 2023)
Newer therapeutic strategies on rise for Prostate Cancer stem cells due to current standardized therapies for prostate cancer including chemotherapy, androgen deprivation therapy (ADT), radiotherapy and surgery are often failed because of tumor relapse ability. Ultimately, tumor relapse develops advanced castration resistant prostate cancer (CRPC), which becomes irreversible and systemic disease. Hence, early identification of intra cellular components and molecular networks that promote prostate cancer is crucial for disease management and therapeutic intervention. One of the potential therapeutic ways for aggressive prostate cancer is to target prostate cancer stem cells (PCSCs), which appear to be a primary mechanism of cancer metastasis and recurrence and are resistant to standardized therapies. Besides, PCSCs have been documented to play a major role in regulating tumorigenesis, sphere formation, and metastasis ability of prostate cancer with their stemness features. Therefore, the current review highlights the origin and identification of PCSCs and their role in antiandrogen resistance as well as stemness related signaling pathways. Besides, the review also focused on the current advanced therapeutic strategies for targeting the PCSCs such as microRNAs (miRNAs), nanotechnology, chemotherapy, immunotherapy, clustered regularly interspaced short palindromic repeats (CRISPR)/ CRISPR associated protein 9 (Cas9) system, and photothermal ablation (PTA) therapy and thus help to attenuate prostate cancer initiation and progression.